DESIGN AND IMPLEMENTATION OF DC-DC CONVERTER CIRCUIT TO CONVERT VOLTAGES IN SOLAR CHARGER CIRCUIT FOR THE APPLICATION ON LAPTOP LOAD - Adhidarma Nugraha, Raditya
Electricity is used in various aspects of life, one of which is to power electronic devices, such as laptop which is used in educational process. However, in Indonesia, there are still areas which do not have access to electricity, thus hindering the education process. On the other hand, Indonesia has tropical climate which is suitable for the use of solar power as a source of electrical energy. In this project, a system was made to provide electricity from solar energy. The system is focused on laptop application with then than 50W power. The system was made of several subsystems, some of which are battery converter, controller converter, and output converter that perform voltage regulation as needed. The battery converter circuit consists of SEPIC circuit that converts the solar panel voltage to battery voltage using the MPPT algorithm. This subsystem was tested by testing the transistor driver circuit, input and output voltage measurements, as well as battery charging experiment using solar panel. On the other hand, the controller converter circuit provides suitable voltages for the control circuits, including the Arduino Nano microcontroller and optocoupler, using LM2596 step down module, MT3068 step up module, relays, and an OR diode logic circuit. Lastly, the output converter circuit converts the battery voltage to 220V AC voltage which is needed by the laptop using a series of buck converter, boost converter, and inverter. This subsystem was tested by testing the input dan output of the buck and boost converters, measuring the output of the system, and experimenting with charging a laptop using the system. From the test results, it can be concluded that the system is able to charge the laptops using energy from solar panels according to the specifications. In addition, an experiment of testing the resilience of the system had also been done and the system has met the IP52 standard.